Ornamental Teaching Gardens: Design, Development, and Use - Sandra B. Wilson; Tara M. Minton; Laurie K. Mecca; Judith Gersony (EDIS)
The teaching gardens at the University of Florida's (UF) Indian River Research and Education Center (IRREC) were developed as an outdoor teaching laboratory to provide on-site plant collections for hands-on learning activities. The educational value of the gardens is witnessed daily by demonstrated landscape design principles and visible plant nomenclature. This is EDIS document FE469, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published January 2004.